(untitled) (American Journal of Pedagogical and Educational Research, 2024)
This article is devoted to the process of conducting a pedagogical experiment in teaching econometrics. In the article, the author also provided information on the types of pedagogical experiments, the results of the experiment, as well as the conclusions and proposals made on its basis.